FORMULASI DAN UJI SIFAT LILIN AROMATERAPI KOMBINASI MINYAK ATSIRI DAUN KEMAFORMULASI DAN UJI SIFAT LILIN AROMATERAPI KOMBINASI MINYAK ATSIRI DAUN KEMANGI (OCINUM SANCTUM L) DAN SEREH (CYMPOGOGON ATRATUSNGI (OCINUM SANCTUM L) DAN SEREH (CYMPOGOGON ATRATUS) - Anggraini, Herlina (Journal of Pharmacy Tiara Bunda, 2025)
In the current conditions of the Covid-19 pandemic, aromatherapy candles have become a necessity for the community as an alternative treatment by utilizing natural ingredients whose popularity is increasing. One of natural ingredients used for aromatherapy is basil and lemongrass. This study aimed to determine whether the essential oil combination of basil leaves (Ocimum sanctum L) and lemongrass (Cymbopogon citratus) can be formulated into aromatherapy candles. The experiment was conducted in the laboratory. The essential oils of basil and lemongrass were gainded from E-Commerce and processed through Thin Layer Chromatography. Silica gel stationary phase, chloroform-benzene mobile phase for basil leaves and toluene-ethyl acetate mobile phase for lemongrass samples. Then the materials (for making aromatherapy candle) were made in three different concentrations of formula I (3%: 20%), formula II (2%: 10%), and formula III (1%: 5%). Test of physical properties of the materials included organoleptic test, test melting point, burn times test and preference test from 20 respondents. The results of the test of the materials for aromatherapy candle showed that there was an affect on the physical properties of aromatherapy candles. Based on the findings of physical properties test, formula III resulted the best because of high melting test point and the longest burning time. Formula I was widely preferred for greater concentration of essential oils